Enyesado para revertir problemas de sodicidad por riego: efecto de fuente y dosis - Chevallier Boutell, J.; Carciochi, Walter; García, G.V.; Diovisalvi, Nicolás; Iglesias, P.; Wyngaard, Nicolás; Crespo, Cecilia; Sainz Rozas, Hernan Rene; Reussi Calvo, Nahuel Ignacio (Asociación Argentina de la Ciencia del Suelo, 2023)
Poster